2018
DOI: 10.1167/iovs.17-23648
|View full text |Cite
|
Sign up to set email alerts
|

Induced Pluripotent Stem Cells Promote Retinal Ganglion Cell Survival After Transplant

Abstract: PurposeThe purpose of this study was to characterize whether induced pluripotent stem cells (iPSCs) affect survival of grafted retinal ganglion cells (RGCs) after transplantation.MethodsFor in vitro studies, human iPSCs were either directly cocultured with mouse RGCs or plated in hanging inserts in RGC cultures for 1 week. For ex vivo studies, RGCs and iPSCs were seeded onto the inner surface of an adult rat retina explant and cultured for 1 week. For in vivo studies, RGCs and iPSCs were intravitreally coinjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 16 publications
2
24
0
Order By: Relevance
“…It remains unclear the extent to which ligand expression is maintained within the mature IPL, but the identification of appropriate dendritic stratification by transplanted primary RGCs suggests that at least some of the necessary signals remain present. 29 Transplanted RGC Survival: Consistent with prior reports documenting limited survival and integration of transplanted RGCs, 26,29 we observed hES-RGC survival rates of 10-30% at one week. Survival was not affected by retinal pre-treatment with pronase E (0.6U/mL), though it was further reduced by pronase E (3U/mL) or collagenase, which also impaired retinal glial activity.…”
Section: Transplanted Rgc Neurite Engraftmentsupporting
confidence: 89%
See 1 more Smart Citation
“…It remains unclear the extent to which ligand expression is maintained within the mature IPL, but the identification of appropriate dendritic stratification by transplanted primary RGCs suggests that at least some of the necessary signals remain present. 29 Transplanted RGC Survival: Consistent with prior reports documenting limited survival and integration of transplanted RGCs, 26,29 we observed hES-RGC survival rates of 10-30% at one week. Survival was not affected by retinal pre-treatment with pronase E (0.6U/mL), though it was further reduced by pronase E (3U/mL) or collagenase, which also impaired retinal glial activity.…”
Section: Transplanted Rgc Neurite Engraftmentsupporting
confidence: 89%
“…A number of groups have transplanted neural-progenitors and RGC precursor cells into rodent eyes with varying degrees of survival, but clear evidence of functional RGC replacement has been elusive. [18][19][20][21][22][23][24][25][26][27] Human ESderived RGCs survive in rat eyes and may localize to the RGC layer (RGCL), though these cells did not extend neurites and were RBPMS-negative. 28 Recently, a pivotal study yielded qualified success in transplanting primary mouse RGCs into rat recipients, documenting relatively rare instances of mature RGC morphology, structural synaptogenesis, and functional electrophysiologic responses to light.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, transplantation of iPSC-RGCs may be less invasive than the iPSC-RPE transplantation technique. Specifically, transplantation of iPSC-RPEs requires a needle to be injected into the sub-retina [56,57], whereas transplantation of iPSC-RGCs requires only an injection into the vitreous cavity [17][18][19][20][21]. We believe that a minimally invasive procedure would reduce the risk of postoperative inflammation and easily prevent the enhancement of immunogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…A better approach to restore vision is focused on functional replacement of RGCs by transplantation such as autologous grafts or allografts using stem cells, and is being studied all over the world [14,18]. Recent studies have reported that in vivo transplanted RGCs in animal models are engrafted into the host retina and respond to light stimulation [17][18][19][20][21]. Cell replacement therapy for RGCs has advanced by leaps and bounds.…”
Section: Introductionmentioning
confidence: 99%
“…Markers are also present in the retina for the reprogrammed retort to differentiation [29]. Retinal ganglion cells transplanted in the retina which is a modified form of stem cells and induced pluripotent stem to encourage their survival in the eye [30]. Mostly degeneration of photoreceptors occur due to the absence of retinal pigment epithelium leading to vision loss, integration of photoreceptors may improve visual function [31].…”
Section: Introductionmentioning
confidence: 99%